Transactional Links Between Teacher–Child Relationship Quality and Perceived Versus Sociometric Popularity: A Three‐Wave Longitudinal Study. Issue 4 (7th January 2014) - De Laet, Steven; Doumen, Sarah; Vervoort, Eleonora; Colpin, Hilde; Van Leeuwen, Karla; Goossens, Luc; Verschueren, Karine
<x xml:space="preserve">Abstract</x> This study examined how peer relationships (i.e., sociometric and perceived popularity) and teacher–child relationships (i.e., support and conflict) impact one another throughout late childhood. The sample included 586 children (46% boys), followed annually from Grades 4 to 6 (Mage.wave1 = 9.26 years). Autoregressive cross‐lagged modeling was applied. Results stress the importance of peer relationships in shaping teacher–child relationships and vice versa. Higher sociometric popularity predicted more teacher–child support, which in turn predicted higher sociometric popularity, beyond changes in children's prosocial behavior. Higher perceived popularity predicted more teacher–child conflict (driven by children's aggressive behavior), which, in turn and in itself, predicted higher perceived popularity. The influence of the "invisible hand" of both teachers and peers in classrooms has been made visible.